HRM practices and employees’ rentention: The perspective of job embeddedness theory - Bibi, Palwasha; Pangil, Faizuniah; Johari, Johanim (2016)
In the current study several HRM practices (performance appraisal, promotional opportunities and job security) have been suggested to explain its impact on employees retention. Previously, other studies have endeavored to consider the impact of HRM practices and employees retention but their results are mostly conflicting, therefore further investigation is needed.Moreover, mediating effect of job embeddedness on the relationship between HRM practices and employees retention has been suggested to be investigated.Furthermore, the use job embeddedness theory may help to better understand the relationship